Treatment and Prevention of Osteoarthritis through Exercise and Sports - Victor Valderrabano; Christina Steiger (Journal of Aging Research)
Osteoarthritis (OA) is a degenerative joint disease with a high prevalence among older people. To date, the pathogenesis of the disease and the link between muscle function and OA is not entirely understood. As there is no known cure for OA, current research focuses on prevention and symptomatic treatment of the disorder. Recent research has indicated that muscle weakness precedes the onset of OA symptoms. Furthermore, several studies show a beneficial effect of land-based aerobic and strengthening exercises on pain relief and joint function. Therefore, current research focuses on the possibility to employ exercise and sports in the prevention and treatment of OA.